Remaking Money for a Sustainable Future - Barinaga Martín, Ester (Bristol University Press, 2024)
EPDF and EPUB available open access under CC-BY-NC-ND licence. Money is central to capitalism and to our many sustainability crises. Could we remake money so as to advance sustainable economies and fair societies? A growing number of scholars, politicians and activists think we can, and they are doing it from the bottom up. This book examines how grassroots groups, municipalities and radical crypto-entrepreneurs are remaking money by designing and organising complementary currencies. It argues that in their novel ideas and governance practices lie the key for building green and inclusive economies. Engaging imaginatively with the future of money, this accessible book will appeal to anyone interested in constructing a more sustainable and just world.